Performance and Predictors of Minimal Disease Activity Response in Patients With Peripheral Spondyloarthritis Treated With Adalimumab. Issue 2 (29th December 2021) - Coates, Laura C.; Abraham, Sonya; Tillett, William; Mease, Philip J.; Ramiro, Sofia; Wu, Tianshuang; Wang, Xin; Pangan, Aileen L.; Song, In‐Ho
Abstract : Objective: To examine the concurrent validity and discrimination of criteria for modified minimal disease activity (MDA) in peripheral spondyloarthritis (SpA) following filter principles of Outcome Measures in Rheumatology (OMERACT) and to determine predictors of modified MDA response. Methods: Four modified MDA versions were derived in the ABILITY‐2 study using the Spondyloarthritis Research Consortium of Canada (SPARCC) enthesitis index or the Leeds Enthesitis Index (LEI) while excluding psoriasis. To assess concurrent validity, modified MDA versions were correlated with Peripheral Spondyloarthritis Response Criteria (PSpARC) remission, Ankylosing Spondylitis Disease Activity Score showing inactive disease (ASDAS ID), and physician global assessment of disease activity. Treatment discrimination was assessed between adalimumab and placebo at week 12. Multiple logistic regression was used to determine baseline predictors of long‐term modified MDA responses and sustained modified MDA. Results: The 4 modified MDA versions showed a stronger positive correlation with PSpARC remission (rtet  > 0.95) versus ASDAS ID (rtet  > 0.75) at week 12 and years 1–3 and were able to show discrimination ( P  < 0.001). Responsiveness was shown at week 12; significantly more patients receiving adalimumab versus placebo achieved all 4 versions of modified MDA. Approximately 40–60% of patients treated with adalimumab achieved modified MDA using the LEI or SPARCC enthesitis index at years 1–3. Achieving modified MDA response after 12 weeks of adalimumab treatment was a robust positive predictor of attaining long‐term modified MDA through 3 years (odds ratio [OR] 11.38–27.13 for modified MDA using the LEI; OR 17.98–37.85 for modified MDA using the SPARCC enthesitis index). Conclusion: All 4 versions of modified MDA showed concurrent validity and discriminated well between adalimumab and placebo treatment groups. Early modified MDA response is a more consistent predictor of long‐term modified MDA achievement than baseline characteristics. The 5 of 6 versions of modified MDA could be an appropriate treatment target in patients with peripheral SpA.